Empowering Educators: Uncovering the Transformative Role of ChatGPT in EFL Pre-Service Teacher Development - Sihombing, Filemon; Kusuma, I Putu Indra; Dewi, Kadek Sintya (Jurnal Penelitian Mahasiswa Indonesia, 2024)
AbstractThis qualitative descriptive research investigates the influence of ChatGPT on the professional development of pre-service teachers specializing in English as a Foreign Language (EFL), with a specific focus on pedagogical innovations. The study, conducted using a phenomenological research approach, involved seven participants enrolled in the "Teaching Campus" program at Ganesha University of Education. The primary objective was to explore the experiences of EFL pre-service teachers in utilizing ChatGPT to enhance their professional growth, particularly in the development of pedagogical innovations. The participants reported notable advancements in pedagogical innovations, encompassing enhancements in the preparation of teaching materials, generation of engaging learning ideas, implementation of diverse teaching strategies, formulation of lesson plans, and increased time efficiency. The study concludes that while ChatGPT positively impacts pedagogical creativity, its implementation requires thorough evaluation and adjustments to align with specific teaching contexts and cater to the needs of students, ensuring its effectiveness in fostering the professional growth of pre-service teachers.